2022
DOI: 10.1038/s41598-022-25789-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and breast and prostate cancer risk in the MCC-Spain study

Abstract: Breast and prostate cancers have been associated with circadian disruption. Some previous studies examined associations of sleep duration and breast or prostate cancer risk though findings remain inconsistent. This study examines associations of a range of detailed sleep characteristics and breast and prostate cancer risk in a large-scale population-based case–control study, MCC-Spain. A total of 1738 incident breast cancer cases, 1112 prostate cancer cases and frequency matched controls (n = 1910, and 1493 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, the reason remains uncleraly, and more high quality RCT to further complement and prove this. The intervention duration ≤ 30 min has a better effect on alleviating depression in breast cancer patients, because with the extension of listening time, the response to two types of auditory stimuli in the human body is different 63 , and the effect of music intervention may be weakened by the timeliness of behavioural habits or distraction of human attention after the intervention duration is higher than 30 min.Intervention duration of 30 min and frequency of 1 time per day had a better effect on depression relief in breast cancer patients 60 , 61 , which may be related to the timeliness of behavioural habits. It may also be that the frequency of intervention once a day can regulate the stress response of the hypothalamic–pituitary–adrenal axis 64 , which has the effect of regulating the spirit, pleasing the heart, and relieving depression in patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the reason remains uncleraly, and more high quality RCT to further complement and prove this. The intervention duration ≤ 30 min has a better effect on alleviating depression in breast cancer patients, because with the extension of listening time, the response to two types of auditory stimuli in the human body is different 63 , and the effect of music intervention may be weakened by the timeliness of behavioural habits or distraction of human attention after the intervention duration is higher than 30 min.Intervention duration of 30 min and frequency of 1 time per day had a better effect on depression relief in breast cancer patients 60 , 61 , which may be related to the timeliness of behavioural habits. It may also be that the frequency of intervention once a day can regulate the stress response of the hypothalamic–pituitary–adrenal axis 64 , which has the effect of regulating the spirit, pleasing the heart, and relieving depression in patients.…”
Section: Discussionmentioning
confidence: 89%
“…It may be that experts choose according to the current physiological and psychological state of each patient and the different personality of the patient so as to solve the emotional problems of the patient in a targeted way 59 , 60 . In terms of intervention cycle, 2–4 weeks is the best effect size for the music intervention cycle 61 , The effect size is moderate when the intervention cycle is less than or equal to 2 weeks, and the effect size is second when the intervention cycle is more than 4 weeks. Qishou Tang also said in the study 62 that the effect of short-term and medium-term interventions is higher than that of long-term interventions 20 , 24 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…They have a GCS of 16 and 38, and a coverage of 16 and 13, respectively. The next two were written by Wendeu-Foyet et al [ 79 ] and Turner et al [ 80 ], which had a GCS of 27 and 0 and a coverage of 13 and 6, respectively. In their review, Deng et al [ 77 ] found that shift work carries a moderate risk of developing prostate cancer.…”
Section: Discussionmentioning
confidence: 99%